2010
DOI: 10.1159/000316262
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hysteroscopic Biopsy in Obtaining Specimens for Cytogenetic Evaluation in Missed Abortion prior to Suction Dilatation and Curettage

Abstract: Aim:To estimate whether hysteroscopic-guided biopsy of gestational sac(s) in first trimester missed abortion increases the sensitivity of detecting aneuploidy compared to washing and careful specimen collection after suction dilatation and curettage (D&C). Materials and Methods:Thirty-five patients with first trimester missed abortion of which 25 underwent 29 suction D&Cs and 10 underwent hysteroscopic-guided biopsy of 12 gestational sacs prior to suction D&C. The karyotype of products of conception specimens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In contrast, [24] found that direct hysteroscopic sampling did not improve the sensitivity of cytogenetics for aneuploidy detection when compared with conventional suction D&C.…”
Section: Author Contributionsmentioning
confidence: 79%
“…In contrast, [24] found that direct hysteroscopic sampling did not improve the sensitivity of cytogenetics for aneuploidy detection when compared with conventional suction D&C.…”
Section: Author Contributionsmentioning
confidence: 79%
“…Spontaneous abortions occur in approximately 10% to 15% of all pregnancies and can be caused by various factors, including anatomic, endocrine, infectious, metabolic, immunologic, hematologic, and chromosomal abnormalities [1]. Pregnancy loss in infertile couples justify efforts to investigate for the underlying cause.…”
Section: Introductionmentioning
confidence: 99%